Two Distinct Mutations Cause Severe Hemophilia B in Two Unrelated Canine Pedigrees - Gu, Weikuan; Brooks, Marjory; Catalfamo, James; Ray, Jharna; Ray, Kunal (Thrombosis and Haemostasis, 1999)
The molecular defects causing severe factor IX deficiency were identified in two distinct canine breed-variants. Both defects were associated with an absence of plasma factor IX coagulant activity and antigen. A large deletion mutation was found in 1 breed variant, spanning the entire 5’ region of the factor IX gene extending to exon 6. An approximately 5 kb insertion disrupted exon 8 of the second breed-variant. This insertion was associated with alternative splicing between a donor site 5’ and acceptor site 3’ to the normal exon 8 splice junction, with introduction of a new stop codon. The resultant transcript lacked most of the factor IX catalytic domain and 3’ untranslated region. Molecular analyses of canine hemophilia B define an experimental model for study of inhibitor formation and gene therapy strategies, and provide insight into spontaneous mutation mechanisms in the factor IX gene and on the X chromosome of mammalian species.